The instrumental role of the urban project in the monumentalization and securitization of the Vila Olímpica de Barcelona (REVISTA NODO, 2019)
The Olympic Village is the emblematic project of the Barcelona urban reform promoted with the 1992 Olympic Games. It was built on an industrial area, which implied the destruction of the architectural heritage and the eviction of the residents of the working class neighborhood that inhabited the area. This urban project made it possible to make the annihilation of the past, in order to set up an adequate environment to maintain order and coexistence in the new neighborhood. The result it is a private residential complex, built to neutralize uncivil practices that attempt against the image of a conflict-free public space and guarantee the security of its properties of its residents. The article analyzes the instrumental role of the urban project to commodify the space and strengthen social control policies conceived under a model of local business management
Keywords: urban project; heritage; privatopia; neoliberal urbanism; public space